A Longitudinal Study of the Reliability of Acupuncture Deqi Sensations in Knee Osteoarthritis. (1st July 2013) - Spaeth, Rosa B.; Camhi, Stephanie; Hashmi, Javeria A.; Vangel, Mark; Wasan, Ajay D.; Edwards, Robert R.; Gollub, Randy L.; Kong, Jian
Abstract : Deqi is one of the core concepts in acupuncture theory and encompasses a range of sensations. In this study, we used the MGH Acupuncture Sensation Scale (MASS) to measure and assess the reliability of the sensations evoked by acupuncture needle stimulation in a longitudinal clinical trial on knee osteoarthritis (OA) patients. The Knee injury and Osteoarthritis Outcome Score (KOOS) was used as the clinical outcome. Thirty OA patients were randomized into one of three groups (high dose, low dose, and sham acupuncture) for 4 weeks. We found that, compared with sham acupuncture, real acupuncture (combining high and low doses) produced significant improvement in knee pain (P = . 025 ) and function in sport (P = . 049 ). Intraclass correlation analysis showed that patients reliably rated 11 of the 12 acupuncture sensations listed on the MASS and that heaviness was rated most consistently. Overall perceived sensation (MASS Index) (P = . 014 ), ratings of soreness (P = . 002 ), and aching (P = . 002 ) differed significantly across acupuncture groups. Compared to sham acupuncture, real acupuncture reliably evoked stronger deqi sensations and led to better clinical outcomes when measured in a chronic pain population. Our findings highlight the MASS as a useful tool for measuring deqi in acupuncture research.